Competition and government procurement in Malaysia - Abd Ghadas, Zuhairah Ariff; Abdul Rahman, Nasarudin; Ahamat, Haniff (Herald National Academy of Managerial Staff of Culture and Arts, 2018)
This paper aims to study the government procurement regime in Malaysia. The main objective of this paper is to analyse the existing policies on government procurement and to analyse the extent to which these policies are designed in line with competitive principles. This is important to ensure that the government procurement system is not opened to corruption, favouritism, and market distortion and achieves its ultimate objective that is to secure ‘the best value for money’. This research relies on both primary and secondary data. The primary data includes legislation, government policy and report, treasury instruction and circulars. The research also refers to journal articles, conference proceedings and reports as part of the secondary data. However, given the nature of the area which is highly sensitive, the research will not conduct empirical study by way of interview or survey to support the research findings. Despite having a comprehensive regulatory framework to oversee government procurement, the research identifies some weaknesses in the current regime which may expose the procurement activities to potential corruption, bias, and market distortion including: 1. Ambiguity in the implementation of some procurement methods; 2. Lack of transparency in some procurement processes; 3. Expansive preferential treatment to Bumiputera; 4. Lack of an effective review and appeal mechanism in the government procurement regime.